Relationship of vegetarianism with body weight loss and ASCVD - Xu, Yani; Yang, Xuening; Yao, Lina; Liu, Yanping; Hao, Panpan (Frontiers in Nutrition, 2024)
The association between a plant-based diet and weight loss and atherosclerotic cardiovascular disease (ASCVD) has not been fully elucidated. We performed a pooled analysis and Mendelian randomization (MR) analysis to investigate this question. We searched for randomized controlled trials on the effects of a plant-based diet on weight loss compared with a non-plant-based diet. In addition, a two-sample MR study was conducted. Instrumental variables (IVs) were obtained from the genome-wide association studies (GWAS) on the exposures, and we obtained summary statistics on the outcomes. The inverse-variance weighted (IVW) method was used as the main analysis and other MR methods were performed as supplementary analyses. Individuals on the plant-based diet lost more weight than the non-plant-based diet group (WMD -0.96 kg; 95% CI: -1.32 to -0.60). Population conditions and energy restriction were identified as the study-level factors that influenced the pooling results in the subgroup analyses. Increased consumption of raw vegetables was significantly associated with lower BMI (IVW, β -0.35, 95% CI: -0.62 to -0.08, p = 0.012) and lower risk of obesity (IVW, OR 0.11, 95% CI: 0.01 to 0.99, p = 0.048), coronary heart disease (IVW, OR 0.44, 95% CI: 0.21 to 0.92, p = 0.029) and myocardial infarction (IVW, OR 0.39, 95% CI: 0.15 to 0.98, p = 0.045) and a higher HDL-C (IVW, β 0.47, 95% CI: 0.24 to 0.70, p = 4×10-5). The present findings suggest that raw vegetable intake is beneficial for weight loss and prevention of ASCVD.